Array - TRI A, ARDIANA (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This research is motivated by the Constitution based on the Indonesian Republic No. 20 of 2003 Article 58 paragraph (1) that the evaluation of learning outcomes of students by educators to monitor the process, progress, and the national education system. Evaluation tool used by the accounting teacher SMA Negeri 1 Puri Mojokerto still unknown level of feasibility and validity. To know that the study aims to determine the evaluation tools used and the reasons for and undertake a feasibility study on the evaluation tool.This research is descriptive research with quantitative approach. Subjects were teachers accounting subjects and objects of research is an evaluation tool used by the teacher. The data used are primary data, daily test questions used by teachers and secondary data are books that relate to the research literature. Research instruments such as interview and questionnaire validation study eligibility. Data analysis techniques, namely the descriptive analysis based on an interview to determine the types and reasons teachers use evaluation tools and questionnaires that are tailored to PSMA study in 2010 that analyzed the Guttman scale and interpretation criteria to determine the feasibility of the evaluation tool.Based on the results of the analysis carried out, it is known that the evaluation tool used by the teacher is testing the written test. Reasons teachers choose accounting material written test is more on the practice of writing and calculating the financial statements. Evaluation tool used by the accounting teacher SMA Negeri 1 Puri Mojokerto can be categorized as unfit for use. Key words: Equipment evaluation, accounting